Human Development, Theories of. - Johnson, Sara K.; Lerner, Richard M.; Herschberg, R.M.; Hilliard, L.J. (Tufts University. Tisch Library., 2016)
Relational developmental systems (RDS) models frame contemporary scholarship in human development – whether ininfancy, childhood, adolescence, adulthood, or late adulthood – and encourage investigations of variation both within timeand across people in their trajectories of individual context relations using person-centered and change-sensitive methods.Accordingly, we contrast RDS theory-framed research with prior theoretical approaches, specifying implications of RDS theories for description, explanation, and optimization of development across the life span. We note implications for programs and policies and for promoting social justice among diverse individuals, families, and communities.